PERLINDUNGAN TERHADAP PEREMPUAN DAN ANAK MELALUI HUKUM ADAT SEBAGAI MANIFESTASI HAK ASAL USUL DALAM TINDAK KEKERASAN TERHADAP PEREMPAN DAN ANAK DI SUMATERA BARAT - Yoserwan Yoserwan (LPPM Universitas Ekasakti Padang, 2023)
Women and children are groups that are vulnerable to acts of violence. National and international laws have provided protection for women and children from acts of violence. In addition, customary law as one of the rights of origin also provides protection. In West Sumatra, protection for women and children is provided through customary law contained in the Undang-Undang nan Salapan and in the Petatah Petitih that exist and lives in society. Through the nagari government, protection is provided through the resolution of acts of violence against women and children through customary settlements of acts of violence that are mild in nature. Meanwhile, serious acts of violence are resolved through the criminal justice system. It is necessary to prepare a nagari regulation to provide a legal basis for optimizing legal protection for women and children that is truly in line with the conditions that exist in customary law communities.